INDIGOFERA: â€œKINI DAN NANTIâ€ - Muzzazinah, Muzzazinah; Chikmawati, Tatik; Rifai, Mien A.; Ariyanti, Nunik Sri (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract- A few people know Indigofera, but as a admirer of batik and tenun, these plant gives hope for the preservation of batik. Indigofera has a variety of benefits , but more commonly known as blue dye in batik and tenun. The problems of restore the glory of Indigofera from Indonesia who had experienced the triumph can be divided into three principal. There are the increasing scarcity of Indigofera plant, the lack of willingness of the community batik for the cultivation, the process of indigo dyeing longer and complicated, and the results of staining with the natural color is not uniform. The problem by the business presence of more efficient synthetic dyes, the price of synthetic dyes is cheaper. While research on Indigofera dye is still limited and stagnate, this is a problem should be a concern Botanist . Keywords: Indigofera, batik, tenun, natural dye